JURIDICAL REVIEW OF REPATRIATION AND BURIAL OF SUSPECT, PROBABLE, AND COVID-19 CONFIRMATION CASES - Olga Indah Suci; Herlina Manullang; Kartina Pakpahan (International Journal of Latin Notary, 2021)
Covid-19 is transmitted through close contact and droplets. People who are most at risk of infection are in close contact with Covid-19 patients or who care for Covid-19 patients and mortuary staff. For this reason, regulating criminal acts, mechanisms, and legal sanctions to the perpetrators of curing and burying the bodies of suspected, probable, and confirmed cases of Covid-19 that are not following the procedures will be discussed in this thesis research.